Pemberian Scaffolding Kepada Siswa SMP dalam Menyelesaikan Soal Pisa Konten Change and Relationship - Loka, Yollanda Dhea Lusfita; Fuad, Yusuf (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
Change and relationship is a content in PISA that is classified as having a low score, because students experience errors in completing it, so to find out the student's mistakes, Newman's analysis is needed which is useful to find out the mistakes made by students, as well as scaffolding efforts to minimize and overcome errors. This study aims to describe the provision of scaffolding to junior high school students in solving PISA content change and relationship problems at Proklamasi Balongbendo Junior High School for the 2022/2023 even semester in April. Of the three classes consisting of classes VIII-a (32 students), VIII - B (31 students), and VIII-C (32 students). Then selected Class VIII-B purposively in this study, consisting of 16 male students and 15 female students. Purposive selection based on, special characteristics in the form of student ability and student activity in the classroom. The tests were conducted on all students of Class VIII - B, namely the initial ability test (TKA) and the PISA Ability Test (TKP). The subjects were selected based on the results of analysis of student answers and scores of initial ability test (TKA) and PISA ability test (TKP) and considering the UAS scores in mathematics subjects of students in semester 1, the subjects consisted of high ability subjects (S1), medium ability subjects (S2), and low research subjects (S3). The results of the study stated S1 able to read the question correctly, can understand the purpose of the problem, explain all the information in the question and be able to understand what is being asked, able to write a plan of completion, by doing pemisalan and using formulas that are in accordance with the solution of the question, mention the conclusions in accordance with the conclusions of the answers obtained from the work done. S2 is able to be able to read the problem correctly, explain what information is obtained from the problem, able to understand what is meant by the problem and write what is known and asked in the problem, able to transform the problem into a mathematical model by making a calculation from the information obtained in the problem, but have difficulty in performing calculation operations so as not to get the correct final result, S2 is able to write conclusions in accordance with the results obtained, but not precisely because the answers obtained are also not precise so that the results obtained in the conclusion are not correct. S3 is able to read the problem correctly, explaining all the information known from the question correctly. S3 does not define formulas and models math. S3 directly perform the overall calculation operation based on the information in the problem. And in the course of the interview the subject said with confidence that there was a proper formula to solve it, but he did not know the formula so did not write it down. S3 is not able to write the final conclusion precisely because the results of the answers obtained are also not appropriate. The type of error S1 in solving the PISA content change and relationship problem is a transformation error, and a process skill error. The types of S2 errors in solving PISA content change and relationship problems are Transformation errors, and process skill errors, and final answer writing (encoding). The types of S3 errors in solving PISA content change and relationship problems are comprehension errors, transformation errors, process skill errors, and final answer writing (encoding). Based on the type of error S1 is transformation, scaffolding given is reviewing, and restructuring. And the type of process skill error, scaffolding given is reviewing, restructuring, explaining. Based on the type of error made by S2 in solving the PISA content change and relationship Problem, the scaffolding transformation error given is reviewing, and restructuring, restructuring. The type of process skill error, scaffolding given is reviewing, and restructuring. Error encoding, scaffolding given is restructuring, and reviewing, restructuring. Based on the type of errors made by S3 in solving the PISA content change and relationship problem, namely understanding errors, scaffolding given is reviewing and process skill errors, scaffolding given is reviewing, developing conceptual reviewing explaining, restructuring. Error encoding scaffolding given reviewing, restructuring, reviewing.